Cancer cachexia: Diagnosis, assessment, and treatment - Sadeghi, Mohammadamin; Keshavarz-Fathi, Mahsa; Baracos, Vickie; Arends, Jann; Mahmoudi, Maryam; Rezaei, Nima (Critical reviews in oncology/hematology, 2018)
•A global consensus on the diagnosis and treatment of cancer cachexia is needed.•This review thoroughly examines the latest updates in cancer cachexia management.•Different cancer cachexia definitions and diagnostic criteria are compared.•Nutritional, muscularity, psychosocial, and biomarker assessments are investigated.•Pharmacologic, nutritional, exercise, and psychosocial treatments are discussed. Cancer cachexia is a multi-factorial syndrome, which negatively affects quality of life, responsiveness to chemotherapy, and survival in advanced cancer patients. Our understanding of cachexia has grown greatly in recent years and the roles of many tumor-derived and host-derived compounds have been elucidated as mediators of cancer cachexia. However, cancer cachexia remains an unmet medical need and attempts towards a standard treatment guideline have been unsuccessful. This review covers the diagnosis, assessment, and treatment of cancer cachexia; the elements impeding the formulation of a standard management guideline; and future directions of research for the improvement and standardization of current treatment procedures.